2024
DOI: 10.1002/brb3.3467
|View full text |Cite
|
Sign up to set email alerts
|

The association between lymphocyte to high‐density lipoprotein ratio and depression: Data from NHANES 2015–2018

Junzhi Chen,
Yan Huang,
Xiaolin Li

Abstract: IntroductionThe relationship of lymphocyte to high‐density lipoprotein ratio (LHR) with depression remains uncertain. We aimed to evaluate the association between LHR and depression in US adults.MethodsIn this cross‐sectional study, a total of 4216 participants were enrolled from the National Health and Nutrition Examination Survey (2015–2018). Depressive symptoms were measured with the Patient Health Questionnaire‐9 (PHQ‐9). Participants were classified as having depression if PHQ‐9 scores were ≥10. Multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have discussed associations between depression and other biomarkers.The association between relative adiposity, an indicator of obesity, and depression was found to be most signi cant in the US adult population in a cross-sectional study conducted by Xianlin Zhu et al (24) . Depression has also been reported to be associated with lymphocyte to HDL ratios, leading to the suggestion that immune dysfunction or in ammatory factors may be a key contributor to depression 25 .NHHR, as an emerging biomarker, has received much attention for its regulation of diseases such as atherosclerosis, diabetes, kidney stones, and periodontitis. Despite the lack of previous studies describing the relationship between NHHR and psychiatric disorders, there have been many reports of NHHR-related markers, including non-HDL, TC, HDL, apolipoproteins, and low-density lipoproteins.Non-HDL cholesterol is the sum of all kinds of lipoprotein cholesterol in the blood except HDL cholesterol, and relevant research investigations have found that apolipoprotein (b) and HDL, the main components of non-HDL cholesterol, are the main lipid metabolism indexes constituting atherosclerosis, and that atherosclerosis is prone to cause endothelial function damage at the beginning, and increase in vascular oxidative stress, which further causes nitric oxide-dependent diminished vasodilatory function, which in turn causes major depressive disorder (26)(27)(28)(29) .Numerous investigations have revealed that lower levels of total cholesterol, LDL and non-HDL increase the risk of depression (30)(31)(32)(33) .It has been suggested that low plasma cholesterol levels can reduce the synthesis of neuromodulators such as steroids, which can lead to depressed mood (34,35) .In a cross-sectional study of the relationship between lipids and depressive episodes in postmenopausal women, it was found that after quintiles of HDL-C and LDL-C were used as continuous variables, it was concluded that lower concentrations of HDL-C and LDL-C were associated with the risk of developing depression (36) .Xianlin Zhu et al analyzed the positive association between non-HDL-C and depression in 42,143 subjects in a cross-sectional study, and the relationship was more signi cant in men (37) .In view of the above relationship between each of the lipid indicators of depression, we believe that it is necessary for the study of the association between NHHR and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have discussed associations between depression and other biomarkers.The association between relative adiposity, an indicator of obesity, and depression was found to be most signi cant in the US adult population in a cross-sectional study conducted by Xianlin Zhu et al (24) . Depression has also been reported to be associated with lymphocyte to HDL ratios, leading to the suggestion that immune dysfunction or in ammatory factors may be a key contributor to depression 25 .NHHR, as an emerging biomarker, has received much attention for its regulation of diseases such as atherosclerosis, diabetes, kidney stones, and periodontitis. Despite the lack of previous studies describing the relationship between NHHR and psychiatric disorders, there have been many reports of NHHR-related markers, including non-HDL, TC, HDL, apolipoproteins, and low-density lipoproteins.Non-HDL cholesterol is the sum of all kinds of lipoprotein cholesterol in the blood except HDL cholesterol, and relevant research investigations have found that apolipoprotein (b) and HDL, the main components of non-HDL cholesterol, are the main lipid metabolism indexes constituting atherosclerosis, and that atherosclerosis is prone to cause endothelial function damage at the beginning, and increase in vascular oxidative stress, which further causes nitric oxide-dependent diminished vasodilatory function, which in turn causes major depressive disorder (26)(27)(28)(29) .Numerous investigations have revealed that lower levels of total cholesterol, LDL and non-HDL increase the risk of depression (30)(31)(32)(33) .It has been suggested that low plasma cholesterol levels can reduce the synthesis of neuromodulators such as steroids, which can lead to depressed mood (34,35) .In a cross-sectional study of the relationship between lipids and depressive episodes in postmenopausal women, it was found that after quintiles of HDL-C and LDL-C were used as continuous variables, it was concluded that lower concentrations of HDL-C and LDL-C were associated with the risk of developing depression (36) .Xianlin Zhu et al analyzed the positive association between non-HDL-C and depression in 42,143 subjects in a cross-sectional study, and the relationship was more signi cant in men (37) .In view of the above relationship between each of the lipid indicators of depression, we believe that it is necessary for the study of the association between NHHR and depression.…”
Section: Discussionmentioning
confidence: 99%